Analysis Of The Quality Of Items for VIII Class IPA Teachers MTs.N I Kota Bengkulu Study Year 2019/2020 - Raden Gamal Tamrin Kusumah; Hadiwinarto Hadiwinarto (Yayasan Darussalam Bengkulu, 2021)
This study aims to analyze the validity, reliability, level of difficulty, differentiation power, and item distractors made by science subject teachers of class VIII MTs.N 1 Bengkulu, Academic Year 2019/2020. Samples were taken by saturated sampling technique. The instrument in this study was a daily test sheet made by a science subject teacher for grade VIII, which amounted to 20 multiple choice questions. Analysis of the construct validity of multiple choice questions in terms of material, construction and language is appropriate, there are several questions that still need to be improved in terms of construction. Analysis of the validity of the UH 1 items showed that 40% of the questions were valid; reliability of 0.76 means that it has high consistency; the difficulty level of the questions was 40% difficult, 55% moderate and 5% easy questions; difference power 45% bad, 35% sufficient and 20% good; 80% of cheaters are functional. At UH 2 60% of the questions are valid; reliability of 0.78 means it has high consistency; 35% for difficult questions and 65% for medium questions; difference power 30% bad, 45% sufficient and 25% good; 75% of cheaters are functioning.